Light Guided Endoscopic Dacryocystorhinostomy - Iftikhar Aslam, Jamshed Nasir (Pakistan Journal of Ophthalmology, 2006)
Purpose: To evaluate the outcome of light guided endoscopic dacryocystorhinostomy (DCR). Material and Methods: Seven patients above the age of 35 years were recruited for the said study at the Combined Military Hospital Lahore. Careful selection of patient and assessment of their lacrimal apparatus status was established with radiological test. All those with Nasolacrimal duct obstruction irrespective of the level of obstruction were included in the study after proper consent. A joint venture by ENT and Eye surgeon involving introduction of fiber optic bright light commonly used for Vitrectomy through the lower canaliculus into the Lacrimal sac directed towards the medial wall of the sac which shines through in the dark room environment from the lateral wall of the nasal cavity and is marked by the surgeon. The mucous membrane and than the bone is removed through a bone cutter and the sac is reached. The sac wall is incised and later intubated for a period of three months. Results: Initial results were encouraging in the form of reduction and disappearance of epiphora. Once the tube was removed, five out of seven patients showed remarkable and two showed moderate improvement in their symptoms of epiphora. A success rate of 100% was achieved as far the patient symptom was concerned. Individual patients were followed for a period of one year, after which a final assessment of their drainage system was made and was found to have satisfactory drainage system and patency. Conclusion: This study demonstrated that good results can be achieved in cases of persistent epiphora due to nasolacrimal duct obstruction with less traumatic surgical procedure under local anaesthesia with equal or better results. A long term follow up is still awaited and we expect to have good outcome once a long term follow up is established. Key words: Dacryocystorhinostomy, Endoscopic dacryocystorhinostomy. Nasolacrimal duct obstruction, Epiphora.